Sull’uso della forza nelle relazioni internazionali - Sperotto, Federico (Rivista di studi politici internazionali, 2010)
In his study, recently published by the «European Journal of International Law», professor Christian Tams examines the developments occurring in the area of extraterritorial use of military force during the last 20 years, to conclude that there is a tendency to see exceptions to the use of force in international law more favourably today than 20 years ago. Building on the analysis of Tams, this article supports the idea that relationships within the community of States, and consequently the right to wage war, or more generally to use military force (jus ad bellum), especially in relation to new global threats, are taking a profile that from «Grotian» goes to «Hobbesian», but that is deemed developing into a third model, which is not the model defined by Bull as «Kantian», but a model where the two traditions, «Hobbesian» and «Grotian» compete in substantial equilibrium, which Sean Murphy describes as a more «Protean jus ad bellum». Dans son étude récente publiée par «European Journal of International Law», le professeur Christian Tams examine les développements survenus dans l’utilisation extraterritoriale de la force militaire au cours des 20 dernières années, pour conclure qu’il y a une tendance globale à voir les exceptions à l’utilisation de la force en droit international plus favorablement aujourd’hui que il y a 20 années. S’appuyant sur l’analyse de Tams, cet article soutient l’idée que les relations au sein de la communauté des États – et par conséquent le droit de faire la guerre, ou plus généralement d’utiliser la force militaire (jus ad bellum), en particulier par rapport aux nouvelles menaces globales – prendent un profil qui de «grotiusien» va devenir «hobbesien», mais que tout cela est en train d’évoluer vers un troisième modèle, un modèle où les deux traditions «grotiusienne» et «hobbesienne» concurrencent dans un équilibre substantiel, décrit par Sean Murphy comme «Protean jus ad bellum». PAROLE CHIAVE: Guerra; Terrorismo; Legittima difesa; Grozio; Hobbes.